Antigen Detection Tests for SARS-CoV-2: a systematic review and meta-analysis on real world data - Riccò, Matteo; Ranzieri, Silvia; Peruzzi, Simona; Valente, Marina; Marchesi, Federico; Bragazzi, Nicola Luigi; Donelli, Davide; Balzarini, Federica; Ferraro, Pietro; Gianfredi, Vincenza; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim Rapid antigen detection (RAD) tests on nasopharyngeal specimens have been recently made available for SARS-CoV-2 infections, and early studies suggested their potential utilization as rapid screening and diagnostic testing. The present systematic review and meta-analysis was aimed to assess available evidence and to explore the reliability of antigenic tests in the management of the SARS-CoV-2 pandemic. Materials and Methods. We reported our meta-analysis according to the PRISMA statement. We searched Pubmed, Embase, and pre-print archive medRxiv.og for eligible studies published up to November 5th, 2020. Raw data included true/false positive and negative tests, and the total number of tests. Sensitivity and specificity data were calculated for every study, and then pooled in a random-effects model. Heterogeneity was assessed using the I2 measure. Reporting bias was assessed by means of funnel plots and regression analysis. Results. Based on 25 studies, we computed a pooled sensitivity of 72.8% (95%CI 62.4–81.3), a specificity of 99.4% (95%CI 99.0–99.7), with high heterogeneity and risk of reporting bias. More precisely, RAD tests exhibited higher sensitivity on samples with high viral load (i.e. <25 Cycle Threshold; 97.6%; 95%CI 94.1–99.0), compared to those with low viral load (≥25 Cycle Threshold; 43.6%; 95% 27.6-61.1). Discussion. As the majority of collected reports were either cohort or case-control studies, deprived of preventive power analysis and often oversampling positive tests, overall performances may have been overestimated. Therefore, the massive referral to antigenic tests in place of RT-qPCR is currently questionable, and also their deployment as mass screening test may lead to intolerable share of missing diagnoses. On the other hand, RAD tests may find a significant role in primary care and in front-line settings (e.g. Emergency Departments). (www.actabiomedica.it)